Toxicity and pharmacokinetic studies of lidocaine and its active metabolite, monoethylglycinexylidide, in goat kids - Venkatachalam D; Chambers P; Kongara K; Singh P (MDPI, 2018)
This study determined the convulsant plasma concentrations and pharmacokinetic parameters following cornual nerve block and compared the results to recommend a safe dose of lidocaine hydrochloride for goat kids. The plasma concentrations of lidocaine and monoethylglycinexylidide (MGX) were quantified using liquid chromatography-mass spectrometry. A total dose of 7 mg/kg body weight (BW) was tolerated and should therefore be safe for local and regional anesthesia in goat kids. The mean plasma concentration and mean total dose that produced convulsions in goat kids were 13.59 ± 2.34 µg/mL and 12.31 ± 1.42 mg/kg BW (mean ± S.D.), respectively. The absorption of lidocaine following subcutaneous administration was rapid with Cmax and Tmax of 2.12 ± 0.81 µg/mL and 0.33 ± 0.11 h, respectively. The elimination half-lives (t½λz) of lidocaine hydrochloride and MGX were 1.71 ± 0.51 h and 3.19 ± 1.21 h, respectively. Injection of 1% lidocaine hydrochloride (0.5 mL/site) was safe and effective in blocking the nerves supplying horn buds in goat kids.
Keywords: disbudding; goat kids; lidocaine hydrochloride; toxicity; pharmacokinetics; 0502 Environmental Science and Management; 0608 Zoology; 0702 Animal Production